PELAKSAANAAN SEKOLAH SIAGA BENCANA DI SD NEGERI 19 KAMPUNG BARU KECAMATAN PARIAMAN TENGAH, KOTA PARIAMAN - Dewi Ramadhan (JURNAL RANDAI, 2020)
The Disaster Preparedness School (SSB) which is an activity to build school communities through strengthening knowledge and attitudes, school policies, emergency response plans, school early warning systems, and resource mobilization based on existing school capacities in anticipating disaster risk. Descriptive research type. Sampling technique with purposive sampling. Based on this purposive sampling technique, researchers determined key informants including the Principal, Deputy Principal, and students. The results showed that: The implementation of the disaster preparedness school program at the 19 Primary Schools in Kampung Baru in Pariaman Tengah District, namely knowledge of attitudes and actions, school policies, school preparedness and resource mobility have been categorized as good. There are obstacles in the implementation of the disaster preparedness school program in the form of lack of funds and the lack of seriousness of students in the activities so that the implementation of the disaster preparedness school program has not run optimally. Efforts to be made in the future by the teacher in charge of disaster preparedness school in the form of increasing the desire of students to learn by motivating and making it more interesting so that students become interested and increase it into extracurricular activities and trying to make a subject.